1 - Epic Battles in Radical Development Theory, Field Research and Praxis: A Celebration of Björn Beckman (1938–2019) - Bangura, Yusuf (Africa Development, 2020)
This article reviews the contribution of Björn Beckman, the Swedish political economist, in the study of development. It addresses three issues. The first is his engagement in theoretical debates on the political economy of development. These focus on the nature of the African state, capitalist development in poor countries, whether the military can act as a revolutionary vanguard in spearheading democratic and progressive social change, neoliberal theory of macro-economic adjustment, and the dynamics of state-civil society relations in advancing development and democracy. The second is his field research work in Ghana and Nigeria. This examines the role of organised farmers and the state in the production and marketing of cocoa in Ghana in the 1960s; the entrenchment of wheat import dependence and the failed project of wheat import-substitution in Nigeria; and the construction of a union-based labour regime in Nigeria’s textile industry that enhanced the bargaining power of unions even as a worsening macro-economic environment and industrial restructuring impacted adversely on employment and wages. The third deals with his collaborative work on a variety of organised interest groups, including labour movements, scholar activists, the Nigerian student movement, and organised informal sector groups. The last part of the article discusses the costs of Björn’s combative style of scholarship.